Fluvalinate-Induced Changes in MicroRNA Expression Profile of Apis mellifera ligustica Brain Tissue - Tianle, Chao; Liuxu, Yang; Delong, Lou; Yunhan, Fan; Yu, He; Xueqing, Shan; Haitao, Xia; Guizhi, Wang (Frontiers in Genetics, 2022)
Fluvalinate is a widely used and relatively safe acaricide for honeybee , but it still has a negative impact on honeybee colonies. Such negative effects may be related to fluvalinate caused the brain nerve tissue damages, and the detailed molecular regulation mechanism of this phenomenon is still poorly understood. In this study, we analyzed the miRNA expression profile changes in the brain tissue of Apis mellifera ligustica by miRNA sequencing after fluvalinate treatment. A total of 1350 miRNAs were found expressed in Apis mellifera ligustica brain tissue, and only 180 of them were known miRNAs on honeybee. Among all known and novel miRNAs, 15 were differentially expressed between at least two of the four time periods before and after fluvalinate administration. Further analysis revealed 5 significantly enriched KEGG pathways of differentially expressed miRNAs (DEMs) potential target genes as key pathways, namely “Hippo signaling pathway-fly”, “Phototransduction-fly”, “Apoptosis-fly”, “Wnt signaling pathway” and “Dorso-ventral axis formation”, which indicates DEMs function may related to cell apoptosis and memory impairment in the fluvalinate treated Apis mellifera ligustica brain, miRNA ame-miR-3477-5p, ame-miR-375-3p and miR-281-x were identified as key miRNAs. Overall, our research provides new insights into the roles of miRNAs in the brain tissue during the process of fluvalinate-induced Apis mellifera ligustica poisoning.